Characterization of Modern and Fossil Mineral Dust Transported to High Altitude in the Western Alps: Saharan Sources and Transport Patterns - Florian Thevenon; Massimo Chiaradia; Thierry Adatte; Christoph Hueglin; John Poté (Advances in Meteorology)
Mineral dust aerosols recently collected at the high-altitude Jungfraujoch research station (N, E; 3580 m a.s.l.) were compared to mineral dust deposited at the Colle Gnifetti glacier (N, E; 4455 m a.s.l.) over the last millennium. Radiogenic isotope signatures and backward trajectories analyses indicate that major dust sources are situated in the north-central to north-western part of the Saharan desert. Less radiogenic Sr isotopic compositions of PM10 aerosols and of mineral particles deposited during periods of low dust transfer likely result from the enhancement of the background chemically-weathered Saharan source. Saharan dust mobilization and transport were relatively reduced during the second part of the Little Ice Age (ca. 1690–1870) except within the greatest Saharan dust event deposited around 1770. After ca. 1870, sustained dust deposition suggests that increased mineral dust transport over the Alps during the last century could be due to stronger spring/summer North Atlantic southwesterlies and drier winters in North Africa. On the other hand, increasing carbonaceous particle emissions from fossil fuel combustion combined to a higher lead enrichment factor point to concomitant anthropogenic sources of particulate pollutants reaching high-altitude European glaciers during the last century.